Pengaruh Budaya Organisasi dan Pemberian Insentif terhadap Kepuasan Kerja Karyawan - Flora Liharni Purba; M. Rajab Lubis; Nadra Ideyani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The aimed of this research is to determine the effect of organizational culture and the provision of incentives on job satisfaction of employees of Astra Credit Companies Medan. The problem is focused on the organizational culture that is run and the incentive system carried out by the company. In order to approach the problem, the theoretical references from Robbins (2012) and Luthans (2011) are used. Measuring tool use is organizational culture scale, incentive provision scale and job satisfaction scale to 92 employees of Astra Credit Companies Medan and conducting quantitative data analysis. Data analysis is done by multiple linear regression analysis. The results of the study indicate that there is a positive influence of organizational culture and the provision of incentives on employee job satisfaction. Thus, it can be concluded that there is an influence of organizational culture and the provision of incentives on employee job satisfaction.